2020
DOI: 10.46542/pe.2020.201.379394
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading pharmacy education to produce practice-ready pharmacists in Lebanon

Abstract: Background: Pharmacy is a steadily evolving profession that brings about changes in practice, where the pharmacist should fulfil novel expanded roles. As such, pharmacy education has to adapt to these local and international changes and follow scientific progress to graduate practice-ready pharmacists. The authors’ objective is to suggest a roadmap with practical solutions to scale-up pharmacy education in Lebanon and produce practice-ready pharmacists with specialised competencies while curbing the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The framework agreed upon consisted of six domains. Domains 0 to 5 were adapted from several studies [ 20 22 ] and documented in a competency framework previously suggested by the Order of Pharmacists of Lebanon (OPL) [ 23 ] and inspired by the FIP Global Competency Framework [ 13 ]. Domain 0 included one set of competencies related to pharmaceutical knowledge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework agreed upon consisted of six domains. Domains 0 to 5 were adapted from several studies [ 20 22 ] and documented in a competency framework previously suggested by the Order of Pharmacists of Lebanon (OPL) [ 23 ] and inspired by the FIP Global Competency Framework [ 13 ]. Domain 0 included one set of competencies related to pharmaceutical knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…The content validity of the items was ensured by using a competency framework previously suggested by the Order of Pharmacists of Lebanon [ 23 ], with an additional domain related to emergency preparedness [ 11 , 14 , 24 , 25 ]. An exploratory factor analysis using the principal component analysis technique was conducted for behaviors based on competencies and domains.…”
Section: Methodsmentioning
confidence: 99%
“…Initial education Core competencies initial suggestion [48] Core competencies framework validation [49] Core competencies assessment [50] Preceptors' skills and competencies framework [51] Specialized competencies suggestion [52] Interprofessional education experience and suggestions [53][54][55] Computer literacy scale validation among pharmacists [56] Continuing education (CE) Continuing education assessment [57] Continuing education preference [58,59] Continuing education value and motivation [60] Job market and workforce situation Workforce oversupply and future projections [10] Mismatch between education and labor market [61] Governance solutions for workforce problems [62] Pharmacy specialties recognition (credentialing) [63] Early career training in Lebanon and benchmarking towards the FIP Global Competency Framework [64] Empathy towards patients among pharmacists [65] Quality of life of pharmacists [66] Burnout among community pharmacists [67,68] Financial situation analysis of pharmacists [69] Community pharmacists' readiness for COVID-19 [70] Physical Health of pharmacists [71] Unapproved suggested laws and decisions Legal documents suggestions by the Lebanese Order of Pharmacists: Clinical pharmacy law; Numerus clausus law, Pharmacy education prolongation, credentials recognition and Early career training [72] Licensure assessment improvement (colloquium) [72] Experiential education organization [73] Ready-to-apply educational project Standards for pharmacy education accreditation & Guidance for pharmacy programs accreditation [74] Practice Good Pharmacy Practice standards suggestion [75] Good Pharmacy Practice assessment [76] Medication safety assessment [77]…”
Section: Sub-domain Referencesmentioning
confidence: 99%
“…In addition, an update of policies and regulations, a cultural reform, and a national pharmacy research strategy were also delineated as essential steps toward modernising pharmacy education (Sacre et al, 2021). A road map with practical solutions was also suggested, where core and specialised competencies were assessed through a licensure examination, to scale-up pharmacy education in Lebanon and produce practice-ready pharmacists (Sacre et al, 2020). Nevertheless, the political and economic downfall, monetary collapse, hyperinflation, depletion of hard currency, and cabinet resignation starting in October 2019, coupled with the consequences of the pandemic, all caused a decline in the country's fortunes and were harsh on the educational system, including pharmacy education.…”
Section: Introductionmentioning
confidence: 99%